Investigating the Effects of Cosmic Rays on Space Electronics - Höeffgen, Stefan K.; Metzger, Stefan; Steffens, Michael (Frontiers in Physics, 2020)
The radiation environment in space has severe adverse effects on electronic systems. To evaluate radiation sensitivity, electronics are tested on earth with different types of irradiation sources. Cosmic rays (CR) are the most difficult to simulate on earth, because CR can have energies up to 1020 eV, with a flux maximum of around 1 GeV/n. However, only particles with energies up to several GeV/nucleon are relevant for radiation effect testing of space electronics due to the negligible fluxes beyond. Traditionally single-event effects of these particles were simulated with heavy ions having energies of only a few MeV/n because for “large” devices only the energy loss, often referred to as linear energy transfer (LET), had to be matched. Heavy ions of such high energies can produce secondary particles through nuclear interactions which can induce additional ionization that leads to adverse effects. The need to investigate these effects has grown since electronic devices now incorporate heavier elements (e.g., Cu, W) close to sensitive elements which can have significantly larger nuclear cross sections than in the 1 to 10 MeV/n energy regime. At the moment there is a large trend in the space community to increasingly use commercial off-the-shelf (COTS) electronic devices. One of the reasons is that many challenging space applications can only be met with COTS devices because there are simply no space-qualified devices [often referred to as High Reliability (HiRel)] available with the necessary performance. Another trend in the evolution of Si-based microelectronic integrated circuits is to create 3-dimensional (3D) structures. There are already commercially available 3D NAND-Flash devices [i.e., a type of non-volatile computer memory that uses floating-gate transistors that resembles a NAND (NOT-AND) gate] with several tens of active layers stacked on top of each other. These structures cannot be tested with low energy ions, due to the large depths of the sensitive volumes alone. For radiation tests ion beams are needed that provide constant LET over the whole stack (> 128 layers). In addition, e.g., in systems in a package, one finds several dies stacked on top of each in a single package. To investigate the aforementioned device types, the beam has to be able to penetrate through all the dies.